Optimization Model of Unsignalized Intersection to Signalized Intersection Using PTV. VISSIM: Study Case in Imogiri Barat and Tritunggal Intersection, Yogyakarta, Indonesia - Muchlisin, (International Journal of Integrated Engineering, 2019)
Intersections, particularly in an urban area, are the most potentially crowded than other road networks. In Yogyakarta, some intersections have no signal. One of them is at the crossroads between the Imogiri Timur and Wirosaban road in Yogyakarta. This study aims to create the optimization of model of an existing condition (without signal) and with a signalized intersection. The software that used in this study is PTV. VISSIM 9.0. PTV. VISSIM is one of the microsimulation programs from PTV Group. One of the advantages of PTV. VISSIM is the model results from the dynamic simulation. The results of this study obtained the model result on existing conditions obtained average queue length of 17.76 m, maximum queue length 125.57 m, and the level of service is LOS (Level of Service) â€œDâ€. The models consist of 3 scenarios by giving traffic lights which are (1) without LTOR (Left Turn on Red), (2) with LTOR and (3) combination between LTOR and widening of the road by 2 m on outlet road. The best result shows that the third scenario with the average queue length is 14.99 m, the maximum queue length is 116.43 m, and the service level is LOS â€œCâ€.